Students' Creative Thinking Skills Based on Metaphysics - zebua, Sri husnayati; Yusmarina, Rina; Kurniawan, Ari; Wibowo, Moh. Ali; Imran, Zulfi (BIRCU, 2024)
This study aims to analyze the creative thinking skills of students based on Spiritual metaphysics in order to determine the factors that influence the student’s creative thinking skills based on Spiritual Metaphysics. The research method is applied qualitatively with a case study method. The research sample is students of Philosophy Science Study Program totaling 20 students. This research was conducted on odd semester Philosophy Study Program students in the 2022/2023 academic year. Data collection techniques using questionnaires and interviews with students. Data analysis techniques by reducing data, presenting data, and drawing conclusions. The results of the analysis were carried out to test the validity of the research data with data triangulation. The results showed a variation in the creative thinking skills of Philosophy students with a low category of 45%, medium 30% and high 25%. The conclusion of the research shows that the factors that influence creative thinking skills are intelligence, knowledge, mindset, personality, motivation, and environment. The implication of the research is that it can determine the appropriate Metaphysics learning model to improve the creative thinking competence of Philosophy students.